Symbological Investigation and Analysis of Fire Motifs in Pre-Islamic Iran: Emphasizing Works of the Median and Achaemenid Periods - Hoori Davoudi; Zahra Hosseinabadi (پیکره, 2022)
Problem Definition: By observing the status of fire and fire-place in the reliefs of works left by the kings of the Medes and Achaemenids, it could be understood that fire had a very high and sacred position in Pre-Islamic Iran. In the works left from this era and also in artistic and ceremonial works, the presence and manifestation of fire in catacombs, public ceremonies of kings, and religious and ritual ceremonies can be observed. Therefore, the question raised in this regard is: “What symbolic concepts does the fire motif have in the Median and Achaemenid periods?”Objective: The aim of this study is to Symbologically investigate and analyze the fire motif in the history of Pre-Islamic Iran (the Median and Achaemenid periods) and the status of this element in the culture and art of this period.Research Method: Considering the historical aspect of the present research, the adopted method is descriptive-analytical. The obtained data were classified and reviewed. The data analysis was carried out using descriptive methods and the presentation of images.Results: The results of the research show that in investigating the remaining motifs of the works related to the Median and Achaemenid periods, the symbolic fire always shows the logic of cleansing evil with good. Fire is the manifestation of Asha (piety and truth) on earth, and the fireplace is the place to worship and praise Ahura Mazda. Also, fire is a symbol of purity and peace of being, benefiting from the property of purifying matter and soul essence. In fact, if the fire was devoid of this characteristic, it could never be the connection between the earthly human world and the spiritual realm of Ahura.